A randomized controlled, trial on effects of mobile phone text messaging in combination with motivational interviewing versus standard infant feeding counselling on breastfeeding and child health outcomes, among women living with HIV - Moleen Zunza; Lehana Thabane; Louise Kuhn; Christine Els; Carl Lombard; Mark F. Cotton; Taryn Young (International Breastfeeding Journal)
Abstract Background Despite efforts to promote optimal breastfeeding practices, the practice of exclusive breastfeeding is low in South Africa. We conducted a trial to determine whether text messaging plus motivational interviewing prolonged exclusive breastfeeding during the first six months of life and improved child health outcomes. Methods We conducted a randomized parallel group-controlled trial between July 2022 and May 2024, at a secondary-level healthcare facility. Mothers living with HIV, 18 years or older, initiating breastfeeding, on combination antiretroviral therapy (cART) and their infants were enrolled. The primary endpoint was exclusive breastfeeding from birth through week 24, based on the consecutive 24-hour food recall interviews. We compared differences in exclusive breastfeeding rates using a proportion test. Mothers who completely stopped breastfeeding were asked an open-ended question on reasons for stopping breastfeeding. Results Using block randomization mother-child pairs (n = 276) were randomly allocated to receive intervention (n = 138) or standard infant feeding counselling (n = 138), of whom 105 and 101 mother-child pairs in the intervention group and standard care group, respectively, completed all four study visits. Exclusive breastfeeding rate at 24 weeks in the intervention group was 6% (6/105) and 7% (7/101) in the standard care group, rate difference − 1% (95% CI -6–4%). Sixty-two of 276 mothers completely stopped breastfeeding, of whom 25% (34/138) and 20% (28) were in the intervention group and standard care group, respectively. The most common reasons for stopping breastfeeding were the mother needing to return to work or look for work, 66% (n = 41). We also found that early breastfeeding cessation increased risk of child hospitalization or death compared to any form of breastfeeding to week 24, 10% (5/48) versus 3% (5/158), p = 0.055. Conclusions We found no effect of the intervention on exclusive breastfeeding rates. Early cessation of breastfeeding was prevalent and maternal employment characteristics are important social determinants of breastfeeding behaviour. There is need for further research evaluating the effect of interventions that include financial incentives on breastfeeding practices among socioeconomically disadvantaged mothers. HIV services should reliably offer cART, consistently monitor viral load, and support mothers cART adherence, in settings where mixed feeding is common. Trial registration The trial was registered on ClinicalTrials.gov (NCT05063240) and Pan African Clinical Trial Registries (PACTR202110870407786) before recruitment of the first subject.